Further discussion on strategic suggestions for promoting the construction of China’s satellite Internet —— Consideration based on the technology route and commercial closed loop of satellite direct connection to mobile phone - YANG Lingcai; ZHAO Dong; YANG Huxiao; LI Yankun; TIAN Ye (Dianxin kexue)
Accelerating the construction of satellite Internet infrastructure and promoting the development of new technologies, new models and new business forms of the digital economy such as satellite direct connection to mobile phone, has become a key development direction of the global information and communication industry. The application of LEO (low earth orbit) constellation direct connection to mobile phone is facing huge technical challenges. China’s satellite Internet technology maturity and commercialization system are not perfect, and it faces the mismatch between different demand and global coverage, industrial investment and commercial return, launch demand and carrying capacity. It was suggested to combine national characteristics, market characteristics, and technology maturity. Give full play to China’s industrial advantages in the field of terrestrial and satellite mobile communications, explore technological evolution routes and commercial development paths suitable for China’s LEO constellation direct connection to mobile phone, promote the connection of innovation chain, technology chain, industrial chain and capital chain, and form an open, efficient, complete and secure satellite Internet industry and business ecology. To construct a satellite Internet construction and operation mode suitable for national conditions, and build a new engine for promoting the development of digital economy and new quality productivity in our country.